A kind of all-day high-performance antifouling composite film and preparation method thereof

By combining the fluorescent substrate with the substrate loaded with Ag-Cu2O and zwitterionic polymer, the problems of low utilization rate of photocatalytic materials and powder material settlement are solved, and high-performance anti-fouling and anti-biological pollution effects are achieved throughout the day, providing new ideas for marine pollution prevention.

CN118578741BActive Publication Date: 2025-02-28WUHAN INSTITUTE OF MARINE ELECTRIC PROPULSION (THE 712TH RESEARCH INSTITUTE OF CHINA STATE SHIPBUILDING CORP LTD)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410760762.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-02-28
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The utilization rate of existing photocatalytic materials is relatively low because the photocatalytic reaction can only be carried out during the day, and the powdered materials are prone to settle and are difficult to directly apply to marine pollution prevention.

Method used

The fluorescent substrate is used to recombinate with the substrate loaded with Ag-Cu2O and zwitterionic polymer. Ag-Cu2O releases reactive oxygen under daylight, and the fluorescent substrate emits fluorescence at night and continuously releases reactive oxygen, achieving pollution protection throughout the day.

Benefits of technology

It achieves high-performance anti-fouling throughout the day, enhances anti-fouling effect, reduces microbial adhesion, provides anti-biological pollution characteristics, and reduces the use of metal ions, making it friendly to the marine environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118578741B_ABST
    Figure CN118578741B_ABST
Patent Text Reader

Abstract

The present invention discloses an all-day high-performance antifouling composite film and a preparation method thereof. The preparation method comprises the following steps: providing a fluorescent substrate, a silver-cuprous oxide composite material, a zwitterionic polymer and a transparent substrate; loading the silver-cuprous oxide composite material and the zwitterionic polymer onto the surface of the transparent substrate to obtain a substrate loaded with the silver-cuprous oxide composite material and the zwitterionic polymer; and compounding the substrate loaded with the silver-cuprous oxide composite material and the zwitterionic polymer with the fluorescent substrate to obtain an all-day high-performance antifouling composite film. The present invention combines the loaded Ag-Cu 2 O and zwitterionic polymer substrates composited with fluorescent substrates, Ag‑Cu 2 O can release active oxygen under daylight for anti-fouling, and continuously release active oxygen at night through the fluorescence emitted by the fluorescent substrate to achieve all-day anti-fouling; in addition, the zwitterionic polymer acts as a protective barrier for the composite membrane, reducing microbial attachment and providing anti-biological fouling properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of marine antifouling composite materials, and specifically relates to an all-day high-performance antifouling composite film and a preparation method thereof. Background Art

[0002] Biofouling is the undesirable accumulation of microorganisms and plants on ship surfaces, pipes and sensors, resulting in increased surface roughness, weight and resistance to navigation. Researchers have recognized the damage caused by biofouling and have begun to develop methods to combat it. Among them, TBT coatings are the most famous polymer coatings with anti-biofouling properties in history. However, due to the discovery of TBT in birds, fish and other organisms, the use of TBT coatings was completely banned in 2008. Therefore, there is an urgent need to develop an environmentally friendly and effective method to prevent biofouling.

[0003] Copper-based chemicals have been widely used in the past to prevent biological growth. However, the extensive leaching of copper has increased the copper concentration in ports and docks, posing risks to marine life and the environment. Zwitterionic polymers contain positively and negatively charged groups and have excellent antifouling properties due to strong surface hydration through electrostatic interactions with water molecules. This hydration layer acts as a spatial and energy barrier, inhibiting the adhesion of proteins and microorganisms. However, the antifouling ability of zwitterionic polymers alone is limited and cannot meet the needs of wider and demanding applications. In recent years, a cost-effective semiconductor-based photogenerated carrier acceleration and separation technology has attracted widespread attention. This technology uses solar energy, is green and low-toxic, and has the potential to prevent marine biofouling. Among the many semiconductor materials, TiO2 is widely used in photocatalysis, but is limited by its absorption range in the ultraviolet region. Cu2O is a semiconductor that can absorb visible light. However, e - / h + The rapid recombination reduces the efficiency of ROS generation, thus affecting the photocatalytic sterilization performance of Cu2O. Depositing noble metals as electron mediators on the photocatalyst can reduce the e - / h + Silver nanoparticles are often used as cheap and effective antibacterial agents. Ag-Cu2O has shown excellent antibacterial properties and improved photocatalytic efficiency, but the powder material is easy to settle and is difficult to be directly applied to marine antifouling. In addition, due to the day-night variation, the photocatalytic reaction in the photocatalytic material can only be carried out during the day, resulting in a low utilization rate of the photocatalytic material. Summary of the invention

[0004] The purpose of the present invention is to overcome the above technical deficiencies, propose an all-day high-performance anti-fouling composite film and a preparation method thereof, and solve the technical problem in the prior art that the photocatalytic reaction can only be carried out during the day, resulting in a low utilization rate of the photocatalytic material.

[0005] In a first aspect, the present invention provides a method for preparing an all-day high-performance antifouling composite membrane, comprising the following steps:

[0006] Providing fluorescent substrates, silver-cuprous oxide composites, zwitterionic polymers, and transparent substrates;

[0007] Loading the silver-cuprous oxide composite material and the zwitterionic polymer onto the surface of a transparent substrate to obtain a substrate loaded with the silver-cuprous oxide composite material and the zwitterionic polymer;

[0008] The substrate loaded with silver-cuprous oxide composite material and zwitterionic polymer is compounded with a fluorescent substrate to obtain an all-day high-performance antifouling composite membrane.

[0009] In a second aspect, the present invention provides an all-day high-performance anti-fouling composite membrane, which is obtained by the preparation method of the all-day high-performance anti-fouling composite membrane according to the first aspect of the present invention.

[0010] Compared with the prior art, the beneficial effects of the present invention include:

[0011] The present invention composites a substrate loaded with Ag-Cu2O and zwitterionic polymers with a fluorescent substrate, so that Ag-Cu2O can release active oxygen for antifouling under daylight, and continuously release active oxygen at night through the fluorescence emitted by the fluorescent substrate to achieve all-day antifouling; in addition, the zwitterionic polymer acts as a protective barrier for the composite membrane, reduces microbial attachment, and provides anti-biological fouling properties. The composite membrane prepared by the present invention has excellent antifouling performance and provides a new idea for the field of marine antifouling. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a SEM image of Ag-Cu2O in the composite film prepared in Example 1 of the present invention;

[0013] Figure 2 The XRD pattern of Ag-Cu2O in the composite film prepared in Example 1 of the present invention;

[0014] Figure 3 This is the UV-vis graph of Ag-Cu2O in the composite film prepared in Example 1 of the present invention;

[0015] Figure 4 The HNMR spectrum of the zwitterionic polymer in the composite membrane prepared in Example 1 of the present invention;

[0016] Figure 5 This is a SEM image of the composite membrane prepared in Example 1 of the present invention;

[0017] Figure 6 This is a SEM image of the composite membrane prepared in Example 2 of the present invention;

[0018] Figure 7 This is a SEM image of the composite membrane prepared in Example 3 of the present invention;

[0019] Figure 8 This is a SEM image of the composite membrane prepared in Comparative Example 4 of the present invention;

[0020] Fig. 9 This is a SEM image of the composite membrane prepared in Comparative Example 6 of the present invention;

[0021] Fig.10 The relative antifouling rates of the composite films prepared in Examples 1-3 and Comparative Examples 1-5 of the present invention;

[0022] Fig.11 Ag in the composite membrane prepared in Examples 1-3 of the present invention after immersion in water for 30 days + (a) and Cu 2+ (b) Release curves; wherein ACZCP-1, ACZCP-0.75, and ACZCP-0.5 correspond to Examples 1-3, respectively;

[0023] Fig.12 The graph is a graph showing the degradation rate of rhodamine b in the composite films prepared in Example 1 of the present invention and Comparative Example 1 under light-dark cycles. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0025] In a first aspect, the present invention provides a method for preparing an all-day high-performance antifouling composite membrane, comprising the following steps:

[0026] S1, providing a fluorescent substrate, a silver-cuprous oxide composite material (Ag-Cu2O), a zwitterionic polymer and a transparent substrate;

[0027] S2, loading the silver-cuprous oxide composite material and the zwitterionic polymer onto the surface of a transparent substrate to obtain a substrate loaded with the silver-cuprous oxide composite material and the zwitterionic polymer;

[0028] S3. Composite the substrate loaded with silver-cuprous oxide composite material and zwitterionic polymer with the fluorescent substrate to obtain an all-day high-performance antifouling composite film.

[0029] The present invention uses the novel idea of ​​composite substrates loaded with Ag-Cu2O and zwitterionic polymers with fluorescent substrates to design antifouling composite membranes, providing a new method for the preparation of all-day high-performance antifouling materials. In the prepared antifouling composite membrane, Ag-Cu2O can release active oxygen for antifouling under daylight, and continuously release active oxygen at night through the fluorescence emitted by the fluorescent substrate to achieve all-day antifouling. In addition, zwitterionic polymers serve as a protective barrier for the composite membrane, reducing microbial attachment and providing anti-biological fouling properties. The present invention not only solves the problem of low utilization of photocatalytic materials when there is no light at night, but also solves the problem of easy sedimentation of powdered materials. The film not only exhibits significantly enhanced antifouling performance, but also reduces the use of metal ions in the coating, is more friendly to marine life and the environment, and has good application prospects in the antifouling effect of hulls and other marine equipment.

[0030] In this embodiment, in step S1, the preparation step of the fluorescent substrate includes:

[0031] S11A, mixing the prepolymer, the curing agent and the fluorescent material uniformly to obtain a semi-cured solution;

[0032] S12A, curing the semi-cured solution to obtain a fluorescent substrate.

[0033] Furthermore, in step S11A, the prepolymer is polydimethylsiloxane.

[0034] Furthermore, in step S11A, the curing agent is Dow Corning DC184.

[0035] The above-mentioned prepolymer and curing agent are widely used encapsulants, which are chemically inert (do not react with phosphors) and have excellent optical transparency and are easy to process and shape.

[0036] Furthermore, in step S11A, the fluorescent material is a long afterglow fluorescent powder. The present invention does not limit the specific type, and those skilled in the art can select it according to actual conditions. For example, it can be SrMgSi2O7 or SrAl2O4. The inventors found in the experiment that the blue fluorescent substrate is more conducive to cooperating with the substrate loaded with Ag-Cu2O and zwitterionic polymer, thereby providing a better antifouling effect.

[0037] Furthermore, in step S11A, in the semi-cured solution, the mass ratio of the prepolymer to the curing agent is 1: (0.08-0.12), further 1: 0.1; the mass ratio of the prepolymer to the fluorescent material is 1: (0.2-1.2), further 1: (0.5-1). If the amount of fluorescent material added is too low, the fluorescent brightness will be affected, and if the amount of fluorescent material added is too high, the substrate will not be cured.

[0038] Furthermore, in step S11B, the curing temperature is 70-90° C., and the curing time is 1-2 hours.

[0039] In this embodiment, in step S1, the preparation step of Ag-Cu2O includes:

[0040] S11B, uniformly dispersing copper salt and polyvinyl pyrrolidone in deionized water, then dropping a reducing agent, centrifuging and drying to obtain Cu2O powder;

[0041] S12B, uniformly dispersing Cu2O powder and silver salt in an alcohol-water mixed solvent, then performing a photoreduction reaction under light, and then centrifuging and drying to obtain nano-Ag-Cu2O powder.

[0042] The present invention prepares Ag-Cu2O through the above method, which has the advantages of simple steps and controllable process.

[0043] Furthermore, in step S11B, the copper salt is at least one of copper nitrate, copper chloride, copper sulfate, and copper acetate.

[0044] Furthermore, in step S11B, the reducing agent is hydrazine hydrate.

[0045] Furthermore, the mass fraction of hydrazine hydrate is ≥80%.

[0046] Furthermore, in step S11B, in the mixed solution system containing copper salt, polyvinyl pyrrolidone and reducing agent, the concentration of copper salt is 0.02-0.1 mol / L, the concentration of polyvinyl pyrrolidone is 10-20 g / L, and the concentration of reducing agent is 0.05-0.15% (v / v).

[0047] Furthermore, in step S12B, in the alcohol-water mixed solvent, the alcohol solvent is at least one of methanol or ethanol.

[0048] Furthermore, in step S12B, in the alcohol-water mixed solvent, the volume ratio of the alcohol solvent to water is 1:(4-9).

[0049] Furthermore, in step S12B, the silver salt is silver nitrate.

[0050] Furthermore, in step S12B, in the mixed solution system containing Cu2O powder and silver salt, the mass ratio of Cu2O powder to silver salt is 100:(5-10), and further 100:(7-8). If the proportion of AgNO3 is too high, a large amount of agglomeration will occur, affecting the performance; if the proportion of AgNO3 is too low, a uniform silver coating layer cannot be formed on the Cu2O surface, which will also cause performance degradation.

[0051] Furthermore, in step S12B, in the mixed solution system containing Cu2O powder and silver salt, the concentration of Cu2O is 1-2 g / L, and the concentration of silver salt is 0.07-0.15 g / L.

[0052] Furthermore, in step S12B, during the photoreduction reaction, the light source is a high-pressure xenon lamp, full-spectrum light, 300-400W xenon lamp, and the irradiation intensity is 200-400mW / cm 2 , the illumination time is 30-90min, and the photoreduction reaction process is carried out under a protective atmosphere. The present invention does not limit the type of protective atmosphere, and those skilled in the art can select it according to actual conditions. For example, the protective atmosphere can be nitrogen, etc.

[0053] In this embodiment, in step S1, the preparation step of the zwitterionic polymer includes:

[0054] S11C, dispersing the zwitterionic monomer into deionized water, then adding an initiator, and performing a polymerization reaction to obtain a zwitterionic polymer solution;

[0055] S12C, the zwitterionic polymer solution is loaded into a dialysis tube, dialyzed in deionized water, and finally freeze-dried to obtain a zwitterionic polymer.

[0056] Furthermore, in step S11C, in the mixed solution system containing the zwitterionic monomer and the initiator, the concentration of the zwitterionic monomer is 0.45-1.15 mol / L, further 0.7-0.9 mol / L; the concentration of the initiator is 0.05-0.1 mg / mL.

[0057] Furthermore, the zwitterionic monomer is a combination of methacryloylethyl sulfobetaine and methacryloyloxyethyl trimethylammonium chloride. Methacryloylethyl sulfobetaine has a highly hydrated layer and can be combined with other polymers by copolymerization, grafting, etc. to further adjust its surface properties and functions; the quaternary ammonium salt group contained in methacryloyloxyethyl trimethylammonium chloride has bactericidal and antimicrobial properties, and can effectively inhibit the growth of microorganisms on the surface. The zwitterionic polymer prepared by the copolymerization of the above two zwitterionic monomers in the present invention combines the super hydrophilicity of methacryloylethyl sulfobetaine (SBMA) and the antimicrobial properties of methacryloyloxyethyl trimethylammonium chloride (MTAC), and the zwitterionic polymer finally obtained has good hydrophilicity and antifouling properties.

[0058] Furthermore, in step S11C, the molar ratio of methacryloylethyl sulfobetaine to methacryloyloxyethyl trimethylammonium chloride is (0.4-3):1.

[0059] Furthermore, in step S11C, the initiator is a K2S2O8 and NaHSO3 initiation system.

[0060] Furthermore, in step S11C, the mass ratio of K2S2O8 to NaHSO3 is 1:(0.5-2), further 1:1.

[0061] Furthermore, in step S11C, before adding the initiator, high-purity nitrogen is bubbled for 30-60 minutes to remove dissolved oxygen.

[0062] Furthermore, in step S11C, the polymerization reaction temperature is 35-40° C., and the polymerization reaction time is 6-12 h.

[0063] Further, in step S12C, the molecular weight cutoff of the dialysis tube is 6000-10000 Da, further 8000 Da.

[0064] Furthermore, in step S12C, the dialysis time is 3-4 days.

[0065] In this embodiment, in step S1, the transparent substrate is selected from at least one of an inorganic non-metallic material and a polymer material. The present invention does not limit the type of the transparent substrate, and those skilled in the art can select it according to actual conditions. For example, the transparent substrate can be silicon dioxide, polyvinyl chloride, polymethyl methacrylate, etc.

[0066] In this embodiment, in step S1, the transparent substrate is also pre-treated before use, and the pre-treatment process includes:

[0067] The transparent substrate is immersed in a Tris-HCl buffer solution containing dopamine, and then washed and dried to obtain a dopamine-modified substrate.

[0068] Furthermore, the concentration of the Tris-HCl buffer solution is 10-100 mmol / L, further 50 mmol / L; the pH is 8-9, further 8.5.

[0069] Furthermore, in the Tris-HCl buffer solution containing dopamine, the concentration of dopamine is 2-4 mg / mL.

[0070] Furthermore, the soaking process is: shaking under air for 12-24 hours.

[0071] Furthermore, the drying temperature is 35-40°C, the drying time is 12-24h, and the drying method is vacuum drying.

[0072] In this embodiment, step S2 includes: uniformly dispersing the silver-cuprous oxide composite material and the zwitterionic polymer in deionized water to obtain a mixed solution, then coating the mixed solution on the surface of a transparent substrate, and then curing, washing, and drying to obtain a substrate loaded with the silver-cuprous oxide composite material and the zwitterionic polymer.

[0073] Furthermore, in the mixed solution, the mass ratio of the silver-cuprous oxide composite material to the zwitterionic polymer is (0.01-0.02): 1. If the Ag-Cu2O concentration is too high, most of the particles will be deposited at the bottom and cannot be evenly dispersed and spin-coated; if the Ag-Cu2O concentration is too low, the antifouling effect is poor.

[0074] Furthermore, in the mixed solution, the concentration of the silver-cuprous oxide composite material is 2-4 mg / mL, and the concentration of the zwitterionic polymer is 200-250 mg / mL.

[0075] The present invention does not limit the coating method, and those skilled in the art can select it according to the actual situation. For example, the coating method can be spin coating, dip coating, spray coating, etc.

[0076] In some specific embodiments of the present invention, spin coating is adopted, and the rotation speed is 1000-1500 rpm and the spin coating time is 120-180 s.

[0077] Furthermore, the curing temperature is room temperature, and the curing time is 12-24 hours.

[0078] The present invention does not limit the compounding method in step S3, and those skilled in the art can choose according to actual conditions. For example, adhesive compounding can be used. In some specific embodiments of the present invention, the adhesive is Ergo 6700.

[0079] In the present invention, it should be noted that the raw materials of the present invention also include their hydrate forms.

[0080] In a second aspect, the present invention provides an all-day high-performance anti-fouling composite membrane, which is obtained by the preparation method of the all-day high-performance anti-fouling composite membrane according to the first aspect of the present invention.

[0081] In the all-day high-performance antifouling composite film of the present invention, the fluorescent substrate emits fluorescence in the dark, which excites Ag-Cu2O to continuously release active oxygen, and finally enables the composite film to have all-day high-performance antifouling performance.

[0082] Example 1

[0083] This embodiment provides a method for preparing an all-day high-performance antifouling composite film, comprising the following steps:

[0084] (1) Preparation of fluorescent substrate: Add 0.5 g of Dow Corning DC184 curing agent to 5 g of polydimethylsiloxane and mix evenly. Then, add 5 g of SrMgSi2O7 to obtain a semi-cured solution. The semi-cured solution is then transferred to a mold and cured at 80°C for 1 hour to obtain a fluorescent substrate with fluorescent properties.

[0085] (2) Preparation of Ag-Cu2O: 0.374 g of copper nitrate and 2 g of polyvinyl pyrrolidone were added to 100 mL of deionized water, stirred evenly, and then 50 μL of hydrazine monohydrate (mass fraction 99%) was added dropwise to obtain a Cu2O colloidal solution, which was then collected by centrifugal drying to obtain Cu2O powder. 100 mg of Cu2O powder and 7 mg of AgNO3 were added to a mixed solution of 90 mL of water and 10 mL of methanol, and the mixed solution was irradiated with a high-pressure xenon lamp for 30 min under a nitrogen environment (350 W xenon lamp, full spectrum light, irradiation intensity 300 mW / cm 2 ), collected by centrifugal drying, and obtained nano-Ag-Cu2O powder with photocatalytic antifouling properties.

[0086] (3) Preparation of zwitterionic polymer: 3.069 g of methacryloylethyl sulfobetaine and 0.828 g of methacryloyloxyethyl trimethylammonium chloride were added to 20 mL of deionized water, and high-purity nitrogen was bubbled for 30 min to remove dissolved oxygen. Then, 0.0005 g of K2S2O8 and 0.0005 g of NaHSO3 were added, and the mixture was polymerized in a vacuum oven at 37 °C for 6 h to obtain a zwitterionic polymer solution. The zwitterionic polymer solution was loaded into a dialysis tube with MWCO = 8000 Da, dialyzed in deionized water for 3 days, and freeze-dried to obtain a zwitterionic polymer with hydrophilicity and antifouling properties.

[0087] (4) Pretreatment of transparent substrate: The polymethyl methacrylate membrane was placed in 10 mL of Tris-HCl (50 mmol / L, pH = 8.5) buffer solution, and then 20 mg of dopamine was added and shaken in air for 12 h. Finally, it was rinsed with deionized water and vacuum dried at 37 °C for 12 h to obtain a dopamine-modified polymethyl methacrylate membrane.

[0088] (5) Loading of Ag-Cu2O and zwitterionic polymer: Add 0.08 g of the Ag-Cu2O powder prepared in step (2) and 4 g of the zwitterionic polymer prepared in step (3) to 20 mL of deionized water to obtain a mixed solution; the mixed solution was dropwise added onto the dopamine-modified polymethyl methacrylate membrane by spin coating at 1000 rpm for 120 s, left for 12 h, rinsed with deionized water, and vacuum dried to obtain a polymethyl methacrylate membrane loaded with Ag-Cu2O and zwitterionic polymer.

[0089] (6) Preparation of composite membrane: The polymethyl methacrylate membrane loaded with Ag-Cu2O and zwitterionic polymer was fixed to the fluorescent substrate prepared in step (1) using Ergo 6700 to obtain an all-day high-performance antifouling composite membrane.

[0090] Example 2

[0091] This embodiment provides a method for preparing an all-day high-performance antifouling composite membrane. Compared with Embodiment 1, the only difference is that step (5) is different, which is as follows:

[0092] (5) Loading of Ag-Cu2O and zwitterionic polymer: Add 0.06 g of the Ag-Cu2O powder prepared in step (2) and 4 g of the zwitterionic polymer prepared in step (3) to 20 mL of deionized water to obtain a mixed solution; the mixed solution was dropwise added onto the dopamine-modified polymethyl methacrylate membrane by spin coating at 1000 rpm for 120 s, left for 12 h, rinsed with deionized water, and vacuum dried to obtain a polymethyl methacrylate membrane loaded with Ag-Cu2O and zwitterionic polymer.

[0093] Example 3

[0094] This embodiment provides a method for preparing an all-day high-performance antifouling composite membrane. Compared with Embodiment 1, the only difference is that step (5) is different, which is as follows:

[0095] (5) Loading of Ag-Cu2O and zwitterionic polymer: Add 0.04 g of the Ag-Cu2O powder prepared in step (2) and 4 g of the zwitterionic polymer prepared in step (3) to 20 mL of deionized water to obtain a mixed solution; the mixed solution was dropwise added onto the dopamine-modified polymethyl methacrylate membrane by spin coating at 1000 rpm for 120 s, left for 12 h, rinsed with deionized water, and vacuum dried to obtain a polymethyl methacrylate membrane loaded with Ag-Cu2O and zwitterionic polymer.

[0096] Example 4

[0097] This embodiment provides a method for preparing an all-day high-performance antifouling composite film, comprising the following steps:

[0098] (1) Preparation of fluorescent substrate: Add 1 g of Dow Corning DC184 curing agent to 10 g of polydimethylsiloxane and mix evenly. Then, add 5 g of SrMgSi2O7 to obtain a semi-cured solution. The semi-cured solution is then transferred to a mold and cured at 80°C for 1 hour to obtain a fluorescent substrate with fluorescent properties.

[0099] (2) Preparation of Ag-Cu2O: 1.87 g of copper nitrate and 1 g of polyvinyl pyrrolidone were added to 100 mL of deionized water, stirred evenly, and then 150 μL of hydrazine monohydrate (mass fraction 99%) was added dropwise to obtain a Cu2O colloidal solution, which was then collected by centrifugal drying to obtain Cu2O powder. 200 mg of Cu2O powder and 15 mg of AgNO3 were added to a mixed solution of 80 mL of water and 20 mL of methanol, and the mixed solution was irradiated with a high-pressure xenon lamp for 30 min under a nitrogen environment (300 W xenon lamp, full spectrum light, irradiation intensity 200 mW / cm 2 ), collected by centrifugal drying, and obtained nano-Ag-Cu2O powder with photocatalytic antifouling properties.

[0100] (3) Preparation of zwitterionic polymer: 1.395 g of methacryloylethyl sulfobetaine and 2.484 g of methacryloyloxyethyl trimethylammonium chloride were added to 20 mL of deionized water, and high-purity nitrogen was bubbled for 60 min to remove dissolved oxygen. Then, 0.001 g of K2S2O8 and 0.0005 g of NaHSO3 were added, and the zwitterionic polymer solution was obtained after polymerization in a vacuum oven at 37 °C for 12 h. The zwitterionic polymer solution was loaded into a dialysis tube with MWCO = 8000 Da, dialyzed in deionized water for 4 days, and freeze-dried to obtain a zwitterionic polymer with hydrophilicity and antifouling properties.

[0101] (4) Pretreatment of transparent substrate: The polymethyl methacrylate membrane was placed in 10 mL of Tris-HCl (50 mmol / L, pH = 8.5) buffer solution, and then 40 mg of dopamine was added and shaken in air for 24 h. Finally, it was rinsed with deionized water and vacuum dried at 37 °C for 24 h to obtain the dopamine-modified polymethyl methacrylate membrane.

[0102] (5) Loading of Ag-Cu2O and zwitterionic polymer: Add 0.06 g of the Ag-Cu2O powder prepared in step (2) and 4 g of the zwitterionic polymer prepared in step (3) to 20 mL of deionized water to obtain a mixed solution; the mixed solution was dropwise added onto the dopamine-modified polymethyl methacrylate membrane by spin coating at 1500 rpm for 180 s, left for 24 h, rinsed with deionized water, and vacuum dried to obtain a polymethyl methacrylate membrane loaded with Ag-Cu2O and zwitterionic polymer.

[0103] (6) Preparation of composite membrane: The polymethyl methacrylate membrane loaded with Ag-Cu2O and zwitterionic polymer was fixed to the fluorescent substrate prepared in step (1) using Ergo 6700 to obtain an all-day high-performance antifouling composite membrane.

[0104] Example 5

[0105] This embodiment provides a method for preparing an all-day high-performance antifouling composite film, comprising the following steps:

[0106] (1) Preparation of fluorescent substrate: Add 1 g of Dow Corning DC184 curing agent to 10 g of polydimethylsiloxane and mix evenly. Then, add 2 g of SrMgSi2O7 to obtain a semi-cured solution. The semi-cured solution is then transferred to a mold and cured at 80°C for 2 hours to obtain a fluorescent substrate with fluorescent properties.

[0107] (2) Preparation of Ag-Cu2O: 0.374 g of copper nitrate and 2 g of polyvinyl pyrrolidone were added to 100 mL of deionized water, stirred evenly, and then 50 μL of hydrazine monohydrate (mass fraction 99%) was added dropwise to obtain a Cu2O colloidal solution. Cu2O powder was collected by centrifugal drying. 100 mg of Cu2O powder and 7 mg of AgNO3 were added to a mixed solution of 90 mL of water and 10 mL of methanol. The mixed solution was irradiated with a high-pressure xenon lamp for 30 min under a nitrogen environment (400 W xenon lamp, full spectrum light, irradiation intensity 400 mW / cm 2 ), collected by centrifugal drying, and obtained nano-Ag-Cu2O powder with photocatalytic antifouling properties.

[0108] (3) Preparation of zwitterionic polymer: 3.069 g of methacryloylethyl sulfobetaine and 0.828 g of methacryloyloxyethyl trimethylammonium chloride were added to 20 mL of deionized water, and high-purity nitrogen was bubbled for 30 min to remove dissolved oxygen. Then, 0.0005 g of K2S2O8 and 0.0005 g of NaHSO3 were added, and the mixture was polymerized in a vacuum oven at 37 °C for 6 h to obtain a zwitterionic polymer solution. The zwitterionic polymer solution was loaded into a dialysis tube with MWCO = 8000 Da, dialyzed in deionized water for 3 days, and freeze-dried to obtain a zwitterionic polymer with hydrophilicity and antifouling properties.

[0109] (4) Pretreatment of transparent substrate: The polymethyl methacrylate membrane was placed in 10 mL of Tris-HCl (50 mmol / L, pH = 8.5) buffer solution, and then 20 mg of dopamine was added and shaken in air for 12 h. Finally, it was rinsed with deionized water and vacuum dried at 37 °C for 12 h to obtain a dopamine-modified polymethyl methacrylate membrane.

[0110] (5) Loading of Ag-Cu2O and zwitterionic polymer: Add 0.04 g of the Ag-Cu2O powder prepared in step (2) and 4 g of the zwitterionic polymer prepared in step (3) to 20 mL of deionized water to obtain a mixed solution; the mixed solution was dropwise added onto the dopamine-modified polymethyl methacrylate membrane by spin coating at 1000 rpm for 120 s, left for 24 h, rinsed with deionized water, and vacuum dried to obtain a polymethyl methacrylate membrane loaded with Ag-Cu2O and zwitterionic polymer.

[0111] (6) Preparation of composite membrane: The polymethyl methacrylate membrane loaded with Ag-Cu2O and zwitterionic polymer was fixed to the fluorescent substrate prepared in step (1) using Ergo 6700 to obtain an all-day high-performance antifouling composite membrane.

[0112] Comparative Example 1

[0113] This comparative example provides a method for forming an antifouling composite film by compounding a substrate loaded with Ag-Cu2O and a zwitterionic polymer with a non-fluorescent transparent substrate. Compared with Example 1, the only difference is that step (1) is different, which is as follows:

[0114] (1) Preparation of non-fluorescent transparent substrate: Add 0.5 g of Dow Corning DC184 curing agent to 5 g of polydimethylsiloxane and mix them evenly. Then transfer the semi-cured solution to a mold and cure it at 80°C for 1 hour to obtain a non-fluorescent transparent substrate.

[0115] Comparative Example 2

[0116] This comparative example provides a method for forming an antifouling composite film by compounding a substrate loaded with Ag-Cu2O and a zwitterionic polymer with a non-fluorescent transparent substrate. Compared with Example 2, the only difference is that step (1) is different, as follows:

[0117] (1) Preparation of non-fluorescent transparent substrate: Add 0.5 g of Dow Corning DC184 curing agent to 5 g of polydimethylsiloxane and mix them evenly. Then transfer the semi-cured solution to a mold and cure it at 80°C for 1 hour to obtain a non-fluorescent transparent substrate.

[0118] Comparative Example 3

[0119] This comparative example provides a method for forming an antifouling composite film by compounding a substrate loaded with Ag-Cu2O and a zwitterionic polymer with a non-fluorescent transparent substrate. Compared with Example 3, the only difference is that step (1) is different, as follows:

[0120] (1) Preparation of non-fluorescent transparent substrate: Add 0.5 g of Dow Corning DC184 curing agent to 5 g of polydimethylsiloxane and mix them evenly. Then transfer the semi-cured solution to a mold and cure it at 80°C for 1 hour to obtain a non-fluorescent transparent substrate.

[0121] Comparative Example 4

[0122] This comparative example provides a method for forming an antifouling composite film by compounding a substrate loaded with a zwitterionic polymer with a fluorescent substrate. The difference between this method and Example 1 is that Ag-Cu2O is not loaded. The details are as follows:

[0123] Loading of zwitterionic polymer: add 4 g of zwitterionic polymer to 20 mL of deionized water to obtain a solution; spin-coat the solution at 1000 rpm for 120 s onto the dopamine-modified polymethyl methacrylate membrane, leave it for 12 hours, rinse it with deionized water, and vacuum dry it to obtain a polymethyl methacrylate membrane loaded with zwitterionic polymer.

[0124] Preparation of composite membrane: The polymethyl methacrylate membrane loaded with zwitterionic polymer was fixed to the fluorescent substrate prepared in step (1) using Ergo 6700 to obtain an antifouling composite membrane.

[0125] Comparative Example 5

[0126] This comparative example provides a method for forming an antifouling composite film by compounding a substrate loaded with a zwitterionic polymer with a non-fluorescent transparent substrate. The difference between this method and Example 1 is that a non-fluorescent transparent substrate is used and Ag-Cu2O is not loaded. The details are as follows:

[0127] Preparation of non-fluorescent transparent substrate: 0.5 g of Dow Corning DC184 curing agent was added to 5 g of polydimethylsiloxane and mixed evenly. The semi-cured solution was then transferred to a mold and cured at 80° C. for 1 hour to obtain a non-fluorescent transparent substrate.

[0128] Loading of zwitterionic polymer: add 4 g of zwitterionic polymer to 20 mL of deionized water to obtain a solution; spin-coat the solution at 1000 rpm for 120 s onto the dopamine-modified polymethyl methacrylate membrane, leave it for 12 hours, rinse it with deionized water, and vacuum dry it to obtain a polymethyl methacrylate membrane loaded with zwitterionic polymer.

[0129] Preparation of composite membrane: The polymethyl methacrylate membrane loaded with zwitterionic polymer was fixed to a non-fluorescent transparent substrate using Ergo 6700 to obtain an antifouling composite membrane.

[0130] Comparative Example 6

[0131] In this comparative example, the dopamine-modified polymethyl methacrylate film prepared in Example 1 was directly used as an antifouling composite film for antifouling testing.

[0132] This group of comparative examples is N2 in the calculation of the anti-algae attachment rate, and is used to calculate the relative antifouling rates of Examples 1-3 and Comparative Examples 1-5.

[0133] Experimental Group

[0134] (1) SEM test: SEM test was performed on the Ag-Cu2O prepared in Example 1 and the composite films prepared in Examples 1-3 and Comparative Examples 4 and 6;

[0135] (2) XRD test: XRD test was performed on the Ag-Cu2O prepared in Example 1;

[0136] (3) UV-vis test: The Ag-Cu2O prepared in Example 1 was subjected to UV-vis test;

[0137] (4) HNMR test: The zwitterionic polymer prepared in Example 1 was subjected to HNMR test;

[0138] (5) Relative antifouling rate test: The test sample was placed in a liquid containing a concentration of 1.2×10 5 Algal cells / ml Microcystis aeruginosa at the bottom of the aquarium were cultured at a constant temperature of 25°C for 30 days with a light cycle of 12 hours daytime / 12 hours nighttime. After the experiment, the samples were removed from the aquarium and washed with deionized water to remove unsettled algae. The surface algae morphology and fluorescence intensity were then recorded using a fluorescence microscope. Five areas on each sample were selected to record the relative fluorescence intensity. The ImageJ software was used to calculate the average fluorescence intensity, providing a quantitative measurement of the relative fluorescence intensity. The anti-algae attachment rate calculation formula is: R=(N2-N1) / N2*100%; wherein R represents the relative antifouling rate, N1 is the average fluorescence intensity of Examples 1-3 and Comparative Examples 1-5, and N2 is the average fluorescence intensity of Comparative Example 6.

[0139] (6) Ion release rate test: In the 30-day day and night cycle antifouling test, 500 μL of the test liquid was extracted from 500 mL of algae solution every 6 days, and the Ag in the liquid was measured using inductively coupled plasma technology. + and Cu 2+ The leaching amount was quantitatively characterized.

[0140] (7) Photodegradation test of rhodamine b: The experimental light source is a 350 W xenon lamp equipped with a 420 nm filter, providing about 200 mW / cm 2of incident light intensity. Each group of samples was placed in a 10 mg / L RhB (100 mL) solution. In order to evaluate the photocatalytic activity of the samples under dark conditions, the experiment was divided into light and dark stages. Before turning on the light source, the samples were magnetically stirred in the dark for 30 minutes to reach adsorption-desorption equilibrium. The light source was then turned on, and the solution was stirred under a xenon lamp for 40 minutes. After 40 minutes, the light source was turned off, and the solution was transferred to a dark environment and stirred for another 40 minutes. 4 mL of the suspension was centrifuged every 20 minutes, and the concentration of RhB was measured using UV-visible spectroscopy.

[0141] See also Figure 1 , Figure 1 This is a SEM image of Ag-Cu2O in the composite film prepared in Example 1 of the present invention. Figure 1 It can be seen that the Ag-Cu2O powder prepared in this embodiment is spherical nanoparticles with a particle size of 100-200 nm.

[0142] See also Figure 2 , Figure 2 The XRD pattern of Ag-Cu2O in the composite film prepared in Example 1 of the present invention is shown in FIG. Figure 2 It can be seen that Ag is successfully deposited on the surface of spherical Cu2O.

[0143] See also Figure 3 , Figure 3 This is the UV-vis graph of Ag-Cu2O in the composite film prepared in Example 1 of the present invention. Figure 3 It can be seen that Ag-Cu2O has excellent photocatalytic performance.

[0144] See also Figure 4 , Figure 4 The zwitterionic polymer prepared in Example 1 of the present invention is characterized by HNMR. Figure 4 It can be seen that the zwitterionic polymer was successfully prepared under this parameter.

[0145] See also Figure 5 , Figure 5 This is a SEM image of the composite membrane prepared in Example 1 of the present invention. Figure 5 It can be seen that a high proportion of Ag-Cu2O nanoparticles are evenly dispersed on the surface of the zwitterionic polymer.

[0146] See also Figure 6 , Figure 6 This is a SEM image of the composite membrane prepared in Example 2 of the present invention. Figure 6 It can be seen that the medium proportion of Ag-Cu2O nanoparticles is evenly dispersed on the surface of the zwitterionic polymer.

[0147] See also Figure 7 , Figure 7This is a SEM image of the composite membrane prepared in Example 3 of the present invention. Figure 7 It can be seen that low-proportion Ag-Cu2O nanoparticles are uniformly dispersed on the surface of the zwitterionic polymer.

[0148] See also Figure 8 , Figure 8 This is a SEM image of the composite membrane prepared in Comparative Example 4 of the present invention. Figure 8 It can be seen that the composite membrane does not contain Ag-Cu2O nanoparticles and is only composed of zwitterionic polymers.

[0149] See also Fig. 9 , Fig. 9 This is a SEM image of the composite membrane prepared in Comparative Example 6 of the present invention. Fig. 9 It can be seen that only dopamine-modified PMMA is formed.

[0150] See also Fig.10 , Fig.10 The relative antifouling rates of the antifouling composite films prepared in Examples 1-3 and Comparative Examples 1-5 of the present invention. Fig.10 It can be seen that Examples 1-3 all have high algae antifouling performance, and Example 1 has the best algae antifouling performance. Specifically, the antifouling performance of Comparative Examples 1-3 decreased by nearly 10-30% compared with Examples 1-3, indicating that the fluorescent substrate (blue) and the substrate loaded with Ag-Cu2O and zwitterionic polymer in the examples are combined to improve the antifouling performance of the composite membrane; at the same time, the antifouling performance of Comparative Example 4 decreased by nearly 30% compared with Example 1, indicating that the introduction of Ag-Cu2O in the examples is conducive to improving the antifouling performance of the composite membrane; in addition, the antifouling performance of Comparative Example 5 decreased by nearly 50% compared with Example 1, reflecting the synergistic antifouling effect of Ag-Cu2O and zwitterionic polymer in the examples.

[0151] See also Fig.11 , Fig.11 This is a graph of the ion release rate of Ag-Cu2O prepared in Example 1 of the present invention in aqueous solution over a period of 30 days. Fig.11 It can be seen that 30 days Ag + The ion release rate is only 0.008 mg / L, Cu 2+ The ion release rate is only 3 mg / L. Compared with direct coating of copper-based materials, the copper leaching of this application is negligible and is environmentally friendly.

[0152] See also Fig.12 , Fig.12 The rate diagram of degradation of rhodamine b by the samples of Example 1 and Comparative Example 1 under light-dark cycle is used to indirectly characterize the release of active oxygen by Ag-Cu2O excited by fluorescence at night. Fig.12It can be seen that after turning off the lights, the concentration of rhodamine b can still be observed to decrease in Example 1, indicating that the fluorescent substrate has the function of maintaining the release of active oxygen at night. After turning off the lights, the concentration of rhodamine b cannot be observed to decrease in Comparative Example 1, indicating that only the transparent substrate cannot maintain the release of active oxygen at night.

[0153] Compared with the prior art, the beneficial effects of the present invention include:

[0154] 1. For the first time, the method based on fluorescent substrate excitation of Ag-Cu2O was used to ensure the ability to continuously release active oxygen throughout the day, effectively improving the problem that the photocatalytic reaction in traditional photocatalytic anti-fouling materials can only be carried out during the day.

[0155] 2. The zwitterionic polymer is assembled with Ag-Cu2O nanocomposite materials to solve the problem of easy sedimentation of powder materials. At the same time, the hydration layer formed by the zwitterionic polymer can effectively block the adhesion of fouling organisms, achieving binary synergistic antifouling and further enhancing the antifouling effect.

[0156] 3. The assembly of Ag-Cu2O nanoparticles and zwitterionic polymers reduces the amount of Ag-Cu2O antifouling powder, is friendly to the marine environment, and is an environmentally friendly and effective method to prevent biological pollution.

[0157] 4. The material continues to emit fluorescence at night, significantly improving the photocatalytic performance at night, effectively enhancing the film's overall anti-fouling ability throughout the day, and opening up a new idea for the design of anti-fouling films.

[0158] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing an all-day high-performance antifouling composite membrane, characterized in that: The following steps are involved: Providing fluorescent substrates, silver-cuprous oxide composites, zwitterionic polymers, and transparent substrates; The silver-cuprous oxide composite material and the zwitterionic polymer are uniformly dispersed in deionized water at a mass ratio of (0.01-0.02):1 to obtain a mixed solution, and then the mixed solution is coated on the surface of a transparent substrate, and then cured, cleaned, and dried to obtain a substrate loaded with the silver-cuprous oxide composite material and the zwitterionic polymer; The substrate loaded with silver-cuprous oxide composite material and zwitterionic polymer is composited with the fluorescent substrate by using an adhesive to obtain an all-day high-performance antifouling composite film; wherein, The preparation steps of the fluorescent substrate include: mixing a prepolymer, a curing agent, and a fluorescent material uniformly to obtain a semi-cured solution; curing the semi-cured solution to obtain a fluorescent substrate; the prepolymer is polydimethylsiloxane; the fluorescent material is at least one of Sr2MgSi2O7 and SrAl2O4; The preparation steps of the silver-cuprous oxide composite material include: uniformly dispersing copper salt and polyvinyl pyrrolidone in deionized water, then dropping a reducing agent, centrifuging and drying to obtain Cu2O powder; uniformly dispersing the Cu2O powder and the silver salt in an alcohol-water mixed solvent, then performing a photoreduction reaction under light, and then centrifuging and drying to obtain nano silver-cuprous oxide composite material powder; in the mixed solution system containing the Cu2O powder and the silver salt, the mass ratio of the Cu2O powder to the silver salt is 100:(5-10); The preparation steps of the zwitterionic polymer include: dispersing a zwitterionic monomer into deionized water, then adding an initiator, and performing a polymerization reaction to obtain a zwitterionic polymer solution; loading the zwitterionic polymer solution into a dialysis tube, dialyzing it in deionized water, and finally freeze-drying it to obtain a zwitterionic polymer; the zwitterionic monomer is a combination of methacryloylethyl sulfobetaine and methacryloyloxyethyl trimethylammonium chloride in a molar ratio of (0.4-3):

1.

2. The method for preparing the all-day high-performance antifouling composite membrane according to claim 1, characterized in that: In the step of preparing the fluorescent substrate, The curing agent is Dow Corning DC184; The mass ratio of the prepolymer to the curing agent is 1:(0.08-0.12); The mass ratio of the prepolymer to the fluorescent material is 1:(0.2-1.2); The curing temperature is 70-90° C., and the curing time is 1-2 hours.

3. The method for preparing the all-day high-performance antifouling composite film according to claim 1, characterized in that: In the preparation step of the silver-cuprous oxide composite material, The copper salt is at least one of copper nitrate, copper chloride, copper sulfate and copper acetate; The reducing agent is hydrazine hydrate, and the mass fraction of the hydrazine hydrate is ≥80%; In a mixed solution system containing copper salt, polyvinyl pyrrolidone and a reducing agent, the concentration of the copper salt is 0.02-0.1 mol / L, the concentration of the polyvinyl pyrrolidone is 10-20 g / L, and the concentration of the reducing agent is 0.05-0.15% (v / v); In the alcohol-water mixed solvent, the alcohol solvent is at least one of methanol or ethanol; In the alcohol-water mixed solvent, the volume ratio of the alcohol solvent to water is 1:(4-9); The silver salt is silver nitrate; During the photoreduction reaction, the light source is a high-pressure xenon lamp, full-spectrum light, 300-400W xenon lamp, and the irradiation intensity is 200-400mW / cm 2 The illumination time is 30-90 min, and the photoreduction reaction process is carried out under a protective atmosphere.

4. The method for preparing the all-day high-performance antifouling composite membrane according to claim 1, characterized in that: In the step of preparing the zwitterionic polymer, In the mixed solution system containing zwitterionic monomer and initiator, the concentration of zwitterionic monomer is 0.45-1.15 mol / L, and the concentration of initiator is 0.05-0.1 mg / mL; The initiator is a K2S2O8 and NaHSO3 initiation system; The polymerization reaction temperature is 35-40°C, and the polymerization reaction time is 6-12h; The molecular weight cut-off of the dialysis tube is 6000-10000 Da, and the dialysis time is 3-4 days.

5. The method for preparing the all-day high-performance antifouling composite membrane according to claim 4, characterized in that: The mass ratio of K2S2O8 to NaHSO3 is 1:(0.5-2).

6. The method for preparing the all-day high-performance antifouling composite membrane according to claim 1, characterized in that: The transparent substrate is also pre-treated before use, and the pre-treatment process includes: The transparent substrate is immersed in a Tris-HCl buffer solution containing dopamine, and then washed and dried to obtain a dopamine-modified substrate; wherein, The concentration of the Tris-HCl buffer solution is 10-100 mmol / L, and the pH is 8-9; In the Tris-HCl buffer solution containing dopamine, the concentration of dopamine is 2-4 mg / mL; The soaking process is: shaking in air for 12-24 hours.

7. The method for preparing the all-day high-performance antifouling composite membrane according to claim 1, characterized in that: In the mixed solution, the concentration of the silver-cuprous oxide composite material is 2-4 mg / mL, and the concentration of the zwitterionic polymer is 200-250 mg / mL; The coating is performed by spin coating, with a rotation speed of 1000-1500 rpm and a spin coating time of 120-180 s; The curing temperature is room temperature and the curing time is 12-24 hours.

8. An all-day high-performance antifouling composite membrane, characterized in that: The all-day high-performance anti-fouling composite membrane is obtained by the preparation method of the all-day high-performance anti-fouling composite membrane according to any one of claims 1-7.

Citation Information

Patent Citations

  • Energy storage photoelectrocatalysis type air purification composite thin film and preparation method thereof

    CN109529954A

  • Surface anticorrosive antifouling coating using polydopamine as base layer as well as modification method and application of coating

    CN110643277A

  • Photocatalyst dispersion and coating liquid

    JP2013193054A